Inheriting Feng Yunhua's Traditional Chinese Medicine nursing thought and application in the Traditional Chinese Medicine breast nursing clinic - LIU, Jing; ZHANG, Furong; ZHANG, Jing; ZHANG, Xuejian; ZHAO, Danfeng; TANG, Ling (Chinese Journal of Integrative Nursing, 2023)
The establishment of Feng Yunhua Traditional Chinese Medicine nursing Inheritance Workstation has proven to be an effective practice of leveraging Feng Yunhua’s thought-Based on core concepts of Traditional Chinese Medicine classics, to promote scientific development of Traditional Chinese Medicine nursing in practice and effectively improve the clinical ability of Traditional Chinese medicine nursing. According to the 14th Five-Year Plan for the Development of Traditional Chinese Medicine Nursing in Beijing, the aim of establishment of Feng Yunhua Traditional Chinese Medicine nursing Inheritance Workstation is to improve the development of Traditional Chinese Medicine breast nursing clinic in perspectives of clinical treatment, technology progress, clinical research and education. (“冯运华中医护理传承工作站”的建立充分发挥中医护理传承导师冯运华“立足中医经典理论核心, 在实践中推动中医护理从经验型向科学型发展, 以切实提高中医护理临床能力为最终目的”的思想内涵, 深度落实《北京市“十四五”中医发展规划》, 促进中医乳腺护理门诊从临床治疗、技术发展与科研教学等多方面的发展。)